When normality collapses from one moment to the next. A sociological theory of singular crisis - Kraemer, Klaus; Steg, Joris (Frontiers in Sociology, 2025)
Since the emergence of sociology, it has been part of the discipline’s self-image to diagnose crises in modern societies. Sociology, however, has no theory that differentiates between normal and extranormal or singular crises. In this article, we want to develop a crisis typology that distinguishes between these two types. While a normal crisis is characterised by cyclical and structural patterns, which usually build up gradually and lead to incremental change, a singular crisis is characterised by eruptive ruptures in relation to the pre-crisis state. Such ruptures can challenge the traditional social order, both institutionally and narratively. Unlike normal crises, a singular crisis is marked by exogenous shocks like wars, natural disasters, or pandemics. This shock marks the beginning of a process of crisis intervention, which we examine to reconstruct the sociological peculiarities of a singular crisis. By using the Covid-19-crisis as an empirical slide, we analyse a singular crisis and list various dimensions and criteria—namely involvement and impact, temporality, principle of order, social change, isomorphism, path dependency, collective morality, mode of legitimation and spatial order—that can be used to differentiate between singular and normal crises.